Expansion of the Central Banks Balances of Developed Countries as the Main Indicator of Looming Global Crisis - Киевич (A.V. Kievich), А.В.; Бухтик (M.I. Buhtik), М.И.; Самоховец (M.P. Samohovets), М.П. (Экономика и банки, 2018)
В статье анализируется рост долговой нагрузки в развитых странах мира и его влияние на политику их центральных банков (ЦБ) в вопросах монетарного стимулирования глобальной экономики; обосновывается тот факт, что ЦБ развитых стран в ближайшем будущем не смогут прекратить монетарное стимулирование и существенно сократить объемы активов на своих балансах без серьезных негативных последствий для мировой экономики. The article analyzes the growth of the debt burden in developed countries and its impact on the policy of their central banks (CB) in matters of monetary stimulation of the global economy and substantiates the fact that the Central Bank of developed countries in the near future will not be able to stop monetary stimulation and substantially reduce the volume of assets on their balance sheets without serious negative consequences for the world economy.